Ensemble of CNN classifiers using Choquet Fuzzy Integral Technique for PCB Defect Classification - Boonchana Purahong; Woranidtha Krungseanmuang; Kasi Tenghongsakul; Tuanjai Archevapanich; ParkPoom Khunthawiwone; Nitjaree Satayarak; Attasit Lasakul (My University, 2024)
This paper presents a novel method for detecting defects in printed circuit boards (PCBs) using an ensemble of classifiers based on the Choquet fuzzy integral. Our approach employs convolutional neural network (CNN) models, specifically ResNet152, VGG19, and InceptionV3 as base classifiers to identify six types of PCB defects: spurs, mouse bites, short circuits, open circuits, spurious copper, and pinholes. Given the critical role of PCBs in ensuring electronic equipment reliability, effective defect detection methods like ours are essential. We employ pre-trained CNN models for feature extraction and classification of PCB defects. Following this, we combine the prediction scores using the Choquet fuzzy integral to derive more accurate final labels, exceeding the accuracy of standalone models. Our approach is tested on PCB images obtained from public repositories, captured using a linear scan CCD. The evaluation results demonstrate average precision, recall, F-score, and accuracy of 93.0%, 95.2%, 95.1%, and 95.1%, respectively.
Keywords: Industrial Vision Systems and Defect Detection